Development of learning media using QuizWhizzer based on ethnomathematics as a learning exercise - Muthmainah, Asma Shofa Nadia; Jihad, Asep; Nurdiansyah, Rikrik (Universitas Maritim Raja Ali Haji, 2024)
The utilization of ethnomathematics-based learning media has driven this research to explore students' understanding of the application of mathematics in daily life. This study aims to (1) Describe how the ethnomathematics-based learning media using QuizWhizzer as a learning exercise is developed; (2) Evaluate the validity of the ethnomathematics-based learning media using QuizWhizzer as a learning exercise; (3) Assess the practicality of the ethnomathematics-based learning media using QuizWhizzer as a learning exercise; (4) To evaluate the effectiveness of the ethnomathematics-based learning media using QuizWhizzer as a learning exercise. The research and development (R&D) method, specifically the ADDIE model, was used for this study. Data sources were obtained from the validation results of media and content experts and eighth-grade students at SMP Negeri 50 Bandung. The findings indicate that (1) The development process adhered to the stages of the ADDIE model; (2) The validation of the mathematics learning media was rated as “highly valid” by both media and content experts; (3) The practicality of the learning media using QuizWhizzer was rated as “highly practical”; (4) The effectiveness of the QuizWhizzer-based learning media was rated as